Toleransi Meja Makan: Bisnis, Budaya Pedagang Kuliner, dan Interaksi Sosial Pedagang di Kota Singkawang - Sri Sudono Saliro; Tamrin Muchsin; Baharuddin Baharuddin (IAIN Palangka Raya, 2021)
This study attempted to analyze the relationship between tolerance values amongst religious followers with culinary trade culture in running a business, which was a hereditary cultural heritage. The interaction activities of culinary traders in Singkawang City were very unique, such as